Child Maltreatment Perform by Mother In Kepulauan Meranti Regency - Novianti, Ria; Febrialismanto, Febrialismanto; Puspitasari, Enda (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Child abuse is an old human history and nowadays we hear it happen more often. The performer of child abuse can be anybody, especially the closest one to children. Work field, social-economic level, and culture differences are some condition that would lead to stress and friction in peopleâs live and for sure, it also affect the child rearing. The most influential person who play role in child rearing is a mother. But in fact, mother also become the performer in child maltreatment. Mother from the low income family often faced more problems and had to struggle to help providing family needs. It leads to stress and affecting the child rearing. In Kepulauan Meranti Regency, eventhough the number of child maltreatment is lower that other Regency in Riau Province, but the number is increasing about 3% per year, but most cases go unreported. The objective of this research is to describe the child maltreatment performed by mother in form of emotional abuse, physical abuse, sexual abuse and neglect. The methodology used is descriptive quantitative approach to describe the form of child maltreatment. Result that can be concluded from the data analysis, the higher percentage of child maltreatment by mother is the physical abuse 57,62%, verbal abuse 51,43%, neglect 42,04% and sexual abuse 26,43%. Stressfull life leads to unappropriate behavior toward child. To prevent it, mother from low income family need support from other member of family and society to decrease stress level and maintain positive child rearing.